THE UTILIZATION OF INFORMATION TECHNOLOGY IN IMPROVING MARKETING PERFORMANCE OF AGRICULTURAL PRODUCTS - Condro Puspo Nugroho; Rini Mutisari; Anisa Aprilia (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
Excess supply on agricultural products tends to occur when the market does not fully utilize their products. In that condition, technology plays an essential role in helping farmers promote and sell their products (e-marketing). In the other hand, applying e-marketing requires specific knowledge and skill by the farmers as the users. Higher knowledge and skill about IT mean a higher chance for farmers to apply e-marketing for their business. This research aimed to identify the level of farmers’ knowledge and skill on using IT and to analyze its impact on the level their income, revenue, and selling price. Location of research was chosen purposively at Malang Regency and Batu City as production areas of horticultural products in Province of East Java. The samples were categorized into two; those were farmers who use e-commerce and those who do not (conventional farmers). The data was analyzed and tested used independent t-test to compare those categories. The results indicated that the level of income, revenue, and selling price were different significantly between those categories of the farmer, in which farmers who used e-commerce received higher income, higher revenue, and higher selling price than the conventional ones.